IMPLEMENTASI KOOPERATIF GI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PASSING BOLA BASKET - ., I Wayan Gede Ari Gunawijaya; ., I Ketut Budaya Astra, S.Pd, M.Or; ., dr. Ni Nyoman Mestri Agustini, S.Ked. (Universitas Pendidikan Ganesha, 2014)
Penelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar teknik dasar passing bola basket melalui implementasi model pembelajaran kooperatif tipe GI pada siswa kelas VIII D SMP Negeri 1 Tegallalang tahun pelajaran 2013/2014. Penelitian ini adalah penelitian tindakan kelas yang dilaksanakan dalam dua siklus dan masing-masing dilaksanakan dalam dua kali pertemuan. Subjek penelitian adalah siswa kelas VIII D SMP Negeri 1 Tegallalang, berjumlah 32 orang dengan rincian 12 orang putri dan 2 orang putra. Data dianalisis menggunakan analisis statistik deskriptif. Hasil analisis data pada siklus I aktivitas belajar teknik dasar passing bola basket secara klasikal sebesar 7 (aktif), dan pada siklus II sebesar 9,06 (sangat aktif). Dari siklus I ke siklus II mengalami peningkatan sebesar 2,06. Persentase hasil belajar teknik dasar passing bola basket secara klasikal pada siklus I sebesar 53,12% (cukup baik), dan pada siklus II sebesar 93,75% (sangat baik). Dari siklus I ke siklus II mengalami peningkatan sebesar 40,63%. Berdasarkan hasil analisis data dan pembahasan disimpulkan bahwa aktivitas dan hasil belajar teknik dasar passing bola basket meningkat melalui implementasi model pembelajaran kooperatif tipe GI pada siswa kelas VIII D SMP Negeri 1 Tegallalang tahun pelajaran 2013/2014. Disarankan kepada guru penjasorkes untuk dapat mengimplementasikan model pembelajaran kooperatif tipe GI dalam proses pembelajaran penjasorkes.Kata Kunci : Pembelajaran GI, aktivitas, hasil belajar, passing, bola basket This research aims at improving the students’ activity and learning outcome in learning Basketball Basic Passing Technique through the implementation of Cooperative Learning Type Group Investigation for the students of grade VIII D SMP Negeri 1 Tegallalang in academic year 2013/2014. This research is a classroom action research, which was carried out in two cycles. Each cycle consisted of two meetings. The subjects of this research were 32 students of grade VIII D SMP Negeri 1 Tegallalang, which consisted of 12 females and 20 males. The data were analyzed through descriptive statistic analysis. The result of data analysis in cycle I showed that the learning activity of Basketball basic passing technique classically was 7 which was categorized as active. In cycle II, the result of students’ learning activity was 9,06, which was categorized as very active. From those results, it can be stated that the result in cycle I increased 2,06 in cycle II. The percentage of students’ learning outcome in learning Basketball basic passing technique classically in cycle I was 53,12%, which was categorized as adequately good. In cycle II, the percentage of students’ learning outcome was 93,75%, which was categorized as very good. It can be stated that the result in cycle I increased 40,63% in cycle II. From the data analysis, it can be concluded that the implementation of Cooperative Learning Type Group Investigation improved the activity and learning outcome in learning Basketball Basic Passing Technique of the students of grade VIII D SMP Negeri 1 Tegallalang in academic year 2013/2014. It is suggested for the teacher of physical exercise to implement the Cooperative Learning Type Group Investigation as their method of instruction in their physical exercise learning process. keyword : GI Learning, activities, learning outcome, passing, Basketball